Better decision-making through mindfulness-based strategic awareness training - REB, Jochen (Institutional Knowledge at Singapore Management University, 2023)
The case is set in June 2021, 15 months into the COVID-19 pandemic. It begins with the CEO of a boutique hotel in Singapore battling mental burnout as he struggled to keep his hard-hit hotel business afloat. He then sought advice from a friend working with the Mindfulness Initiative@SMU and was recommended the Mindfulness-Based Strategic Awareness Training (MBSAT). MBSAT is a course designed specifically for executives who wish to improve their decision-making through a heightened sense of strategic awareness to derive good outcomes. It is particularly suitable for organisation leaders and individuals who aspire to acquire skilful decision-making abilities. Through an eight-session program that teaches formal and informal mindfulness techniques to enhance mental clarity, the key objective of MBSAT is to increase personal well-being, thus resulting in a flourishing life. The case proceeds with five participants of the previous course runs sharing their experiences, their interpretation of mindfulness, and the MBSAT interventions they found useful. It also details how they managed workplace stress, navigated the decision-making process, and coped with COVID-19-related challenges. The case ends with the protagonist feeling excited about the potential benefits mindfulness training could bring to the workplace. He then mulled over the possibility of introducing mindfulness to his organisation. Students will be able to define the concept of mindfulness and explain its importance in the workplace, its positive impact on leaders and employees, as well as the challenges of mindfulness practice. They will understand how MBSAT helps individuals become better decision-makers while avoiding pitfalls. The case also provides the opportunity for them to share their mindfulness experience and hear about real-world examples of corporate mindfulness programmes at large organisations.